Виявлення шумоподібних кодів з проміжним перетворенням в аналоговий сигнал - Погрібний, В. О.; Рожанківський, І. В.; Лозинський, В. І. (Видавництво Національного університету «Львівська політехніка», 2001)
The method of transformation of binary code sequences into an analog signal with the following reproduction of them by means of sign delta modulation (SignDM) for the further detection by the digital matching filtration has been proposed. The results of imitating modeling and recommendations for the choice of parameters of code sequences, smooth filter and SignDM-coder are given.